2018
DOI: 10.1590/1678-5150-pvb-5449
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da lactatemia e das enzimas musculares de equinos Quarto de Milha submetidos à prova de laço em dupla com diferentes tipos de treinamento

Abstract: RESUMO: O objetivo do trabalho foi avaliar a influência de diferentes tipos de treinamento sobre o condicionamento físico de equinos por meio da determinação do lactato sanguíneo e da atividade sérica de creatina quinase, aspartato aminotransferase e lactato desidrogenase após exercício físico de alta intensidade e curta duração. Amostras de sangue venoso foram obtidas de 16 equinos da raça Quarto de Milha, divididos em dois grupos: grupo de treinamento regular (GTR) e grupo de treinamento esporádico (GTE), em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, it also collaborates for the fibromuscular development of the athlete horse, especially the IIA type fiber, that has good oxidative capacity (SANTIAGO et al, 2013). Pereira et al (2018) observed in double roping horses that exercised in regular training, that lactate decreased after 30 min. They considered this to be a positive effect of training on the physical conditioning of the animals.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, it also collaborates for the fibromuscular development of the athlete horse, especially the IIA type fiber, that has good oxidative capacity (SANTIAGO et al, 2013). Pereira et al (2018) observed in double roping horses that exercised in regular training, that lactate decreased after 30 min. They considered this to be a positive effect of training on the physical conditioning of the animals.…”
Section: Resultsmentioning
confidence: 93%
“…In both the pull and helper horse groups the lactate plasmatic concentration increased in T1, differentiating from T0 and T2 (P<0.05) (table 2). Increase in blood lactate after high intensity short duration exercise was also observed in horses shortly after vaquejada (BINDA et al, 2016;SOUZA et al, 2019), barrel racing (RODRIGUES et al, 2016;SOUZA et al, 2018;GOMES et al, 2019;GOMES et al 2020a;Gomes et al, 2020b) and double roping (PEREIRA et al, 2018). Increase in lactic acid can lead to fatigue or early muscle damage and is more common in athletes little conditioned to the type of exercise (VERMEULEN et al, 2017).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation